Annotated checklist of moths of Zambia (Insecta: Lepidoptera) - Mbata, Keith J.; de Prins, Jurate (Zootaxa, 2023)
An annotated checklist of moths was compiled for Zambia based on intensive and extensive reviews of the literature on insects of the country and on field surveys undertaken by the study for a period of five years from March 2013 to October 2017 to confirm some of the literature review records documented. The checklist contains 1,816 species of moths, arranged into 907 genera and 35 subspecies. One hundred and fifty of these moth species are endemic in Zambia. During our biodiversity field surveys, we verified the existence in Zambia of 3.07% of moth taxa reported in the literature. Some species of moths recorded to occur in Zambia are of traditional/nutritional value to some local ethnic groupings in the country. In addition to their use in traditional medicinal concoctions with plants to treat human maladies, some moth larvae or caterpillars serve as extra sources of animal protein and are consumed as snacks and/or relish by the local people. About one percent (0.9%) of all moth species recorded to occur in Zambia and 7.59% of species of the family Saturniidae serve as extra sources of animal protein for some tribes in the country. To date, no moth species in the country has been assessed for the IUCN Red List of Threatened Species. This present checklist will serve as a basis for future governmental decisions on the policy of environmental protection, Red List preparation, and management of natural food security issues in Zambia.